Stigma Kafir pada Jamaah Ahmadiyah di Kabupaten Garut: Studi Kasus tentang Konflik Pendirian Rumah Ibadah - Neng Via Siti Rodiyah; Nisa Ulmatin; Mohamad Dindin Hamam Sidik (Jurnal Iman dan Spiritualitas, 2021)
Houses of worship are an essential religious means for every religious people. In addition to being a "symbol" of religiosity, houses of worship are also a means of broadcasting religious teachings. Religious conflicts related to the establishment of houses of prayer again occurred in Garut Regency. In Indonesia, history records that one of the potential sources of conflict that often leads to arson and destruction is establishing houses of worship. People needed to revitalize local wisdom in their respective regions. This research was conducted with a qualitative approach by taking location in Nyalindung Village, Cilawu District, Garut Regency, West Java. The results of the study found that various riots befall Ahmadiyah pilgrims because there are also many radical groups in Garut. The number of Ahmadiyya worshippers who often hide to conduct religious activities because of citizens' fears does not accept a dispute. The stigma of infidels makes them suspicious. The situation is getting worse as law enforcement turns a blind eye to intimidation. As a compound area, Garut Regency is not spared from the conflict of establishing houses of worship. However, most Muslims in Nyalindung Village are still not tolerant of minorities.